2015
DOI: 10.1016/j.cjtee.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic diaphragmatic rupture with combined thoracoabdominal injuries: Difference between penetrating and blunt injuries

Abstract: Diagnosis of blunt TDR can be easily obtained by radiograph or helical CT scan signs of diaphragmatic hernia. For penetrating TDR without hernia, "offside sign" is helpful as initial assessment. CT scan with coronal/sagittal reconstruction is an accurate technique for diagnosis. All TDR require operation. Penetrating injury has a relatively better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 15 publications
2
35
0
8
Order By: Relevance
“…The reported incidence of TDI ranges from 0.8-7% in patients presented with blunt trauma [25] and 10-15% for penetrating injuries [19]; in our study it was 0.5% and 4%, respectively. The contemporary literature suggests that the left hemi-diaphragm is the most frequent site of diaphragmatic rupture followed by right and bilateral TDIs [1,3,21,27]. The ratio of RTDI-to-LTDI grossly varies in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of TDI ranges from 0.8-7% in patients presented with blunt trauma [25] and 10-15% for penetrating injuries [19]; in our study it was 0.5% and 4%, respectively. The contemporary literature suggests that the left hemi-diaphragm is the most frequent site of diaphragmatic rupture followed by right and bilateral TDIs [1,3,21,27]. The ratio of RTDI-to-LTDI grossly varies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes the most recent TDI studies from different countries [1,3,[14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, we may underestimate the incidence of TDI as the majority of mild (missed) or severe (died before diagnosis) lesions can be difficult to diagnose or because of the unavailability of routine postmortem examination in the state of Qatar.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between the abdominal and thoracic approach in chronic lesions in percentage is shown in Figure 4C. Thoracotomy Abdominal approach with requirement for thoracic assess: only six studies 1,12,27,39,63,66 reported abdominal onset in a total of 385 patients, with subsequent need for thoracic cavity opening in 39 of them (10% CI 95% 8-14%) ( Figure 5A). …”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Причинами возникновения посттравматической диафрагмальной грыжи являются открытая или закрытая травма грудной клетки и живота, торако-абдоминальное ранение и ятрогенные повреждения [2,10,12,14,18]. Некоторыми авторами используется понятие «ложная грыжа», из-за того, что эта грыжа не всегда имеет грыжевой мешок [3].…”
Section: Introductionunclassified
“…Некоторыми авторами используется понятие «ложная грыжа», из-за того, что эта грыжа не всегда имеет грыжевой мешок [3]. Чаще оказывается повреждённым левый купол диафрагмы, а право-сторонняя локализация дефекта составляет лишь 11-14 % [1,3,4,12,14,15,19].…”
Section: Introductionunclassified